2019
DOI: 10.1177/0883073818821035
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin as Adjunctive Treatment for Focal Onset Seizures in Pediatric Patients: A Randomized Controlled Trial

Abstract: Efficacy and safety of pregabalin as adjunctive treatment for children (aged 4-16 years) with partial-onset seizures, hereafter termed focal onset seizures for this study, was evaluated. This double-blind, randomized, placebo-controlled, international study had 3 phases: 8-week baseline, 12-week double-blind treatment (2-week dose escalation; 10-week fixed dose), and 1-week taper. Selection criteria included experiencing focal onset seizures and receiving a stable regimen of 1 to 3 antiepileptic drugs. Study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 14 publications
6
28
1
Order By: Relevance
“…Pregabalin 7 mg/kg/d did not show improvement in V‐EEG log e (24‐hour seizure rate + 1) from baseline to end of study in comparison with placebo ( P = .461; Figure 2). The lack of efficacy seen at the lower dose of pregabalin in these children, aged 1 month to <4 years, is similar to the observation seen in older children (4‐16 years) reported from a previously published study . Although the reduction in seizure frequency with lower doses in both studies was not significant, the impact of the relatively high placebo effect in the studies may confound evaluation of the lower doses of pregabalin studied.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Pregabalin 7 mg/kg/d did not show improvement in V‐EEG log e (24‐hour seizure rate + 1) from baseline to end of study in comparison with placebo ( P = .461; Figure 2). The lack of efficacy seen at the lower dose of pregabalin in these children, aged 1 month to <4 years, is similar to the observation seen in older children (4‐16 years) reported from a previously published study . Although the reduction in seizure frequency with lower doses in both studies was not significant, the impact of the relatively high placebo effect in the studies may confound evaluation of the lower doses of pregabalin studied.…”
Section: Discussionsupporting
confidence: 82%
“…The safety and tolerability assessment indicated that pregabalin administered at both 7 mg/kg/d and 14 mg/kg/d was well tolerated within this pediatric population. Consistent with the clinical trial of children aged 4 to 16 years, the most common TEAE in both pregabalin groups in this trial was somnolence. However, in contrast to older children, weight gain and increased appetite were not commonly reported in children under 4 years.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations